Evaluasi Pengalaman Mahasiswa di Fakultas Kesehatan terhadap Penggunaan Learning Management System menggunakan User Experience Questionnaire - Untoro Dwi Raharjo; Anastasia Suci Sukmawati; Rizky Yuspita Sari (Journal on Education, 2025)
The utilization of digital technology, particularly Learning Management Systems (LMS), has become a critical element in online learning within higher education, including health education. This study aims to evaluate the user experience of the LMS at the Faculty of Health, Universitas Jenderal Achmad Yani Yogyakarta. The research adopts a descriptive quantitative approach with a cross-sectional design, involving 201 active students using Moodle LMS. Data collection was conducted using the User Experience Questionnaire (UEQ), which analyzes six main dimensions: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The results showed that the UEQ dimensions scored highly, indicating that the LMS is an attractive, easy-to-understand, efficient, and reliable online learning platform. The stimulation dimension received relatively good scores; however, the novelty dimension scored lower, indicating a lack of innovative features in the LMS. Benchmarking against similar systems placed this LMS above average in most dimensions. Overall, user experience with the LMS at the Faculty of Health, Universitas Jenderal Achmad Yani Yogyakarta, is generally positive, especially in functional aspects. However, improvements are needed in the areas of novelty and emotional stimulation to enhance the learning experience. Optimizing the LMS design and implementing more interactive learning strategies are recommended.